Reason, religion, and the Australian polity - Chavura, Stephen A. (Routledge studies in modern history, 2019)
Foundations: church and state in Ancien Régime Britain -- The brief rise and fall of the Australian colonial established church -- The coming of plural establishment -- The separation of church and state -- Education, religion, and citizenship -- A secular constitution? The Federation debates -- The moral economy of the early Australian commonwealth -- Civil religion: from civic Protestantism to the Anzac tradition -- Citizenship, the nation, and religion -- Christian Australia: resurgence and retreat -- Culture, gender, sexuality: dechristianising the secular? -- Conclusion: beyond the secular-religion divide -- Beyond the secular-religion Divide.